VALUTAZIONI METRICHE DI PIATTAFORME APR PER RILIEVI E MODELLAZIONI 3D - Lo Brutto, Mauro; Garraffa, Alessandra; Meli, Paola (GEOmedia, 2015)
The paper describes the work conducted for the metric evaluation of areal blocks acquired using different APR systems for Cultural Heritage surveys. The work was carried out on two sites whit different extent and morphology. Two different APR systems (a multi-rotor and a fixed- wing) were used